Visual scanning of social stimuli in preterm and autism spectrum disorder children - Vivian Renne Gerber Lederman; Ana Lucia Goulart; Juliana Gioia Negrão; José Salomão Schwartzman (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: To evaluate the pattern of eye-gaze of preterm (PT), autism spectrum disorder (ASD) and neurotypical (Ty) children. Methods: A cross-sectional study with eight preterm (born with ≤2000 g weight), nine ASD and five Ty male children, between six and nine years old, was performed. The eye gaze was evaluated presenting a board with a couple in social interaction, and a video with four children playing with blocks, projected in a screen computer, successively, evaluating the time that the children looked at each stimulus. Results: Although all the groups focus on the central social figure with no significant differences, ASD presented significant differences in time fixation of the objects (p=0.021), while premature children fixated more time in the central social interaction than in the whole scene than typical children. Conclusions: Although this study found noteworthy differences in the eye-gaze patterns among the three groups, additional research with a more extensive participant pool is necessary to validate these preliminary results.